Does continuous supervision improve teacher’s pedagogical competence? - Ardi Winata; Muhammad Kristiawan; Rambat Nur Sasongko; Sudarwan Danim (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The purpose of this study is to provide a comprehensive picture of the importance of continuous supervision in the context of optimizing teacher pedagogic competence. In this study, a mixed method was used. This research is also known as population research, because all the teachers on duty at SMP Negeri 2 Cengal, namely 28 people, are the research sample. To obtain accurate data, the instruments are arranged according to indicators of pedagogical competence, namely understanding of students, design & implementation of learning, development of students and evaluation of student learning outcomes. Data analysis was carried out according to this research method, there was a qualitative and quantitative analysis with the stages of data reduction analysis, data display which was then verified so that it became a research conclusion. According to the findings of this study, at least there has been an increase in teacher competence as a result of continuous supervision. This research is unique in that it is tested continuously for several periods of supervision, not just once to determine the effect of the implementation of supervision on teacher performance and competence. The final average obtained in each supervision related to the teacher's pedagogic competence is 77.05; 77.75 and 78.8. Of course, these results can help strengthen policies that regulate the implementation of supervision in every educational institution.